Comparative Analysis of Veneral Diseases Diagnosed Using Tree and Certainty Factor Method - Gustri Wahyuni, Elyza; Kurniawan, Ricky (International Journal of Engineering and Technology, 2018)
The danger that can be generated from venereal diseases is, even infertility can lead to death. However, if the disease can be detected as early as possible by doing intense treatment of this disease can be more controlled and even cured. there have been several similar studies that examine the diagnosis of venereal disease, but no studies have tried to examine how effective the methods are applied to diagnose venereal diseases. So in this study wanted to compare the level of effectiveness of previous research with Decision Tree and Certainty Factor method. It was found that by comparative analysis Decision Tree and Certainty Factor methods show more effective system output if the system is made using Decision tree and Certainty Factor compared using Decision Tree only. It can be seen through the calculation using a Likert scale that shows the percentage of 92% (Strongly Agree).Â Â